PENGEMBANGAN MODEL PEMBELAJARAN KETERAMPILAN BERBAHASA INDONESIA BERKONTEKS MULTIKULTURAL - Ida Zulaeha (LITERA, 2013)
This study aims to produce a model of Indonesian language skill learning with multicultural contexts. It employed a research and development design and the tryout was conducted through action research. The model of  multicultural learning integrated into the Indonesian language subject is divided into four stages, i.e. orientation/apperception, exploration, concept finding, and application. The model is supplemented by a learning package guide, a syllabus, lesson plans, learning materials, and evaluation. The model has a sequence consisting of six stages, i.e. orientation, hypothesis, definition, exploration, proof, and generalization. The model has been tried out in three schools in Central Java.